Residue dynamics of imidacloprid, spirotetramat and tebufenpyrad on solanaceous crops - Dubey, J K; Chauhan, Avinash; Devi, Nisha; Sharma, Ajay; Katna, Sapna; Patyal, SK (Indian Journal of Plant Protection, 2020)
The residue dynamics of imidacloprid, spirotetramat and tebufenpyrad were studied on three solanaceous vegetables viz tomato, chilli and brinjal during the year 2014. All the three pesticides were sprayed twice at 10 days intervals on the respective crops. These pesticides were sprayed at the recommended rate (RR) and double the recommended rate (DRR). Fruit and soil samples were collected, extracted and purified by QuEChERS method. High-performance liquid chromatography with a photodiode array detector was used for analysis of imidacloprid, spirotetramat and its metabolite spirotetramat-enol which revealed that the initial deposits of imidacloprid on chilli and spirotetramat on brinjal declined below the determination limit on 7th and 10th day of application at RR and DRR, respectively. Whereas, in soil samples collected after 15th and 20th day of application, respectively, on their respective crops, the residues were below the limit of determination. Residues of tebufenpyrad on tomato fruits persisted up to 7th and 10th day after its application at RR and DRR as analyzed using gas chromatograph with mass spectrometry. The fortification studies of tested substrates revealed a recovery of 90.40 – 111.60% with acceptable RSD of 0.65 – 9.65. Residue evaluation of imidacloprid and spirotetramat irrespective of crops recommends PHI of 6-11 days at their limit of determination (LOD) at RR and DRR. On the basis of data it is evident that the harvest of the crop could be done after 7 days of last application at the recommended dose to safeguard the interest of consumers.